Endovascular Embolisation of Visceral Artery Pseudoaneurysms - Yasir Jamil Khattak; Tariq Alam; Rana Hamid Shoaib; Raza Sayani; Tanveer-ul Haq; Muhammad Awais (Radiology Research and Practice)
Objective. To evaluate the technical success, safety, and outcome of endovascular embolization procedure in management of visceral artery pseudoaneurysms. Materials and Methods. 46 patients were treated for 53 visceral pseudoaneurysms at our institution. Preliminary diagnostic workup in all cases was performed by contrast enhanced abdominal CT scan and/or duplex ultrasound. In all patients, embolization was performed as per the standard departmental protocol. For data collection, medical records and radiology reports of all patients were retrospectively reviewed. Technical success, safety, and outcome of the procedure were analyzed. Results. Out of 46 patients, 13 were females and 33 were males. Mean patient age was 44.79±13.9 years and mean pseudoaneurysm size was 35±19.5 mm. Technical success rate for endovascular visceral pseudoaneurysm coiling was 93.47% (n=43). Complication rate was 6.52% (n=3). Followup was done for a mean duration of 21±1.6 months (0.5–69 months). Complete resolution of symptoms or improvement in clinical condition was seen in 36 patients (80%) out of those 45 in whom procedure was technically successful. Conclusion. Results of embolization of visceral artery pseudoaneurysms with coils at our center showed high success rate and good short term outcome.